Never go home : a novel - Swann, Christopher, 1970- (Crooked Lane Books, 2022)
"Orphaned at age ten by a violent home invasion, Susannah Faulkner grew up wild, her stubbornness the only thing harder than her heart. Since then, she's used her skills to put a boot in the faces of those who deserve it. She knows she's wired wrong and living a dangerous and violent life, but she's determined to wring something decent from the world before she leaves it. Then she gets word her brother Ethan needs her help and returns home to Atlanta. But in the airport, she finds her Uncle Gavin suffering a heart attack. Before he is rushed to the hospital, Gavin whispers a single word to Suzie: Peaches. She's determined to uncover the meaning behind the cryptic message, but Ethan is also deep in trouble. An ex-soldier and ex-con named Finn appeared on his doorstep with a disturbing story: fifteen years earlier, Finn served with their father in Iraq, where they stole millions in cash. Now the money is missing, and Finn wants his share--or else. A gang war threatens to explode on Atlanta's streets. Uncle Gavin clings to life in the hospital. Finn is bent on finding his missing millions. And now, Suzie will be tested as never before in a crucible of violence where all that she holds dear is on the line" --